"FOMO Effect" dalam E-Marketing: Live Shopping dan Flash Sale terhadap terhadap Niat Beli Konsumen Gen Z - Wisnu Rayhan Adhitya; Tiara Reizsa Adhitya (Jurnal ILMAN (Jurnal Ilmu Manajemen), 2025)
This study aims to analyze the impact of Live Shopping and Flash Sale on Generation Z consumers' Purchase Intention, specifically focusing on the role of the "FOMO Effect" (Fear of Missing Out) as a primary driver within the e-marketing context. Employing a quantitative approach, data were collected from 100 Generation Z student respondents from the University of North Sumatra and Medan State University through online questionnaires. The data were analyzed using multiple linear regression after conducting validity, reliability, and classical assumption tests. The findings indicate that both Live Shopping and Flash Sale significantly and positively influence Generation Z consumers' Purchase Intention, both partially and simultaneously. This understanding is reinforced by the notion that the Fear of Missing Out (FOMO) phenomenon serves as a key mechanism, whereby the urgency, perceived scarcity of offers, and exclusive interactive experiences inherent in live shopping and flash sale sessions trigger Generation Z consumers to make purchases. The two variables collectively explain 28.5% of the variance in purchase intention. The implications of this study highlight the importance for marketers to design e-marketing strategies that leverage elements of urgency, scarcity, and direct interaction to effectively activate the "FOMO Effect" and boost purchase intention among the digitally savvy Generation Z target market.